The Legitimacy of the Government in the Political, Legal and Economic Space of Modern Russia: Features of Understanding of the Socio-cultural Reasons - Mordovtsev, Andrey Yu.; Mamychev, Alexey Y.; Mordovtseva, Tatyana V.; Plotnikov, Andrey A. (International Journal of Economics and Financial Issues, 2016)
The article presents theoretical-methodological foundations of social and cultural interpretation of the nature of legitimacy of power. The authors present arguments for the importance of the transition research the government as a whole, its institutions, processes of legitimation and legalization of the national legal system from class or liberal principles and heuristic schemes to different cultural methodologies using hermeneutic methods in the study of Russian political and legal reality. In this context, the article presents and analyses aspects of the modern conservative legal discourse. It should be noted that modern legal literature is taking place several basic approaches to the understanding of its essence: institutional and sociological neo-institutional. Each of these methods of treatment of political (or rather, the state-legal) regime is valuable because it reveals the one or the other aspect of it, so these three approaches allow to reveal the essence of the institutions of state and legal regime and its special functional nature. Any economic model that does not properly solve the problem of inequality eventually will face a crisis of legitimacy. Unbalanced market and the state will not allow the interaction of the economy to overcome the social and political instability, which in turn will harm the long-term economic growth and well-being (Nouriel Roubini). Keywords: political and legal organization of society, socio-cultural factors, national leader of the legal mentality, political regime, state power JEL Classification: M14, G30, D72, K40